Effects of culture conditions on the production of antagonistic substance produced by Bacillus cereus 357 - YU Fei-jin; CHEN Wei-liang (浙江大学学报. 农业与生命科学版)
In order to study the factors which affect the growth and the antagonistic substance production of B. cereus 357, the culture media and conditions were studied. Six media of KMB, PDA, LB, Davis, SMA and Danbo were prepared, and the growth of Bacillus cereus 357 and the antagonistic activity produced by this bacteria were detected after cultured on these six media at different conditions. The results showed that B. cereus 357 grew best and produced the highest antagonistic activity after cultured on KMB medium, i. e. KMB medium was the appropriate medium for the growth and antagonistic substance production. There were no differences on the antagonistic activity when B. cereus 357 was cultured on the KMB solid medium or liquid medium. The antagonistic activities reached highest when B. cereus 357 was cultured at 37℃ and pH7.5 or at the logarithm growth later period. The studies of culture conditions will be helpful for the isolation and purification of the antagonistic substance produced by B. cereus 357 in large scale in future.